Literature Review: Mekanisme Resistensi Kemoterapi Berbasis Platinum - Amelia Rizky Khalidah (Politeknik Kesehatan Tanjung Karang, 2020)
Cisplatin is a type of platinum-based chemotherapy that is often used in the spectrum of solid neoplasms, including the ovaries, testicles, urinary vesicles, colorectal, lungs, and head-neck. The clinical success of platinum-based chemotherapy, however, is limited to side effects and the incidence of treatment resistance. Resistance has limited the efficacy of these agents in most diseases, so further knowledge is needed on how the resistance mechanism can occur so that further development can be carried out. Molecular mechanism of cisplatin resistance. Malignant cells can lose their sensitivity to the cytostatic/cytotoxic activity of cisplatin as a result of genetic or epigenetic damage. These changes can affect processes that precede the actual binding of cisplatin to its targets (pre-target resistance), potentiating the cell's ability to repair molecular damage caused by cisplatin (resistance at the target level) and damaging the signal transmission that usually imparts damage caused by cisplatin in apoptosis (post-target resistance) or stimulates pro-survival signaling that counteracts the cytotoxicity of cisplatin even though it usually does not occur by this drug (target resistance).